0 Deepak BoraNewbie Asked: July 25, 20202020-07-25T22:11:45+05:30 2020-07-25T22:11:45+05:30In: IIT If |9y−6| =3, then y2 −4y/3 is 0 GATE 2016, Aerospace Engineering Share Facebook 1 Answer Voted Oldest Recent Deepak Bora Newbie 2020-07-25T22:20:52+05:30Added an answer on July 25, 2020 at 10:20 pm |9y−6| = 3 9y-6 = 3 9y = 3 + 6 9y = 9 y = 1 Now, y2-4y/3 put y=1 2-8/3 -2/3 Therefore y2-4y/3 = -2/3 1 Reply Share Share Share on Facebook Share on Twitter Share on LinkedIn Share on WhatsApp Leave an answerLeave an answerCancel reply Featured image Select file Browse Add a Video to describe the problem better. Video type Youtube Vimeo Dailymotion Facebook Choose from here the video type. Video ID Put Video ID here: https://www.youtube.com/watch?v=sdUUx5FdySs Ex: "sdUUx5FdySs". Click on image to update the captcha. Save my name, email, and website in this browser for the next time I comment. Related Questions Limit at infinity Argument of a Complex Number Binomial Theoreom How can we remember formulas in mathematics.? What is the value of radian ?